ETNOMATEMATIKA DALAM UPACARA ADAT NAEK DANGO SUKU DAYAK KANAYAT KABUPATEN LANDAK PADA MATERI BANGUN RUANG SISI LENGKUNG - Eko Saputra; Hongki Julie (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The Naek Dango Traditional Ceremony is a traditional ceremony of the Dayak Kanayat community in Merayuh Village, Air Besar District, Landak Regency, West Kalimantan Province. This study aims to explore ethnomathematics in the ceremony. Through ethnomathematics exploration, various mathematical concepts contained in the Naek Dango Traditional Ceremony can be identified, such as measuring volume and surface area. This research is a qualitative study with an ethnographic approach. The subjects of this study were the Temenggung and the Traditional Head of Merayuh Village. Data were obtained through active collection and analysis by the researcher. The collected data were analyzed through data condensation, data presentation, and continuous drawing of conclusions. The results of this study indicate that there is ethnomathematics in the Naek Dango Traditional Ceremony which is shown through the activities of calculating, determining locations, measuring, designing, playing, and explaining.